Independence from the perspective of the Shari'ah Committee - Zainal Abidin, Nor Hafizah; Mat Yasin, Fatimah; Zainal Abidin, Ahmad (Emerald Publishing Limited, 2020)
Purpose – Being the gatekeeper of Shari’ah compliance and holding the responsibilities to mitigate Shari’ah non-compliance risks are among the main roles of the Shari’ah Committee members. The purpose of this study is to gather perceptions of the Shari’ah Committee members on what and how they safeguard and strengthen their independence in fact and independence in appearance in practice. Design/methodology/approach – Data were gathered through semi-structured interviews that were conducted with thirteen Shari’ah Committee members from respective IFI. Findings – Based on the Islamic worldview and agency theory, the findings posited that safeguard measures within the context of Shari’ah Committee were strengthened by the presence of competencies, personal characters of the Shari’ah committee members, board engagement, role of chairman and accountability to God. Based on the theory, it was suggested that, the characteristics of Shari’ah committee and presence effective governance structure able to minimise threats to independence and enhance Shari’ah Committee effectiveness. Originality – This study contributes to the evidence on safeguard measures in Malaysian contexts that is highly regulated in governing Shari’ah governance practices in IFIs that could be considered by other Shari’ah Committees in different contexts. Practical implications – The insights from this study underlines other fit and proper criteria that need to be considered and enhanced to ensure the independence of the Shari’ah committee members when performing their roles and responsibilities for the IFIs. Besides, approaches of board engagement and Chairman involvement in overseeing the Shari’ah committee in discharging its duties able to improve its independence in fact and in appearance.